Case Report of Nonfamilial Cherubism in a Toddler: Description of Clinic-Radiographic Features and Osseous-Dental Treatments - Mitra Karbasi Kheir (Case Reports in Medicine)
Cherubism is a rare familial disease that occurs between the ages two and five years and regresses after puberty. Most of the cherubism cases show familial history, but there are some cases without familial histories of disorder. A two-year-old boy with a painless symmetrical progressive swelling of the jaws had visited maxillofacial radiology department. Panoramic radiograph revealed well-defined multilocular, radiolucent areas of both jaws. Computed tomography of the jaws showed well-defined, bilateral, multilocular, expansile lesions with thinning of cortical plate of maxilla and mandible and displacing the unerupted first molar anteriorly. Clinical, radiologic, and histopathologic characteristics confirmed the diagnosis of cherubism.